2022
DOI: 10.1080/17461391.2022.2119434
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and surface electromyography analyses reveal an intensity dependent active stretch‐shortening cycle of the vastus lateralis muscle during ergometer rowing

Abstract: A rowing cycle is characterised by a stretch-shortening cycle (SSC) at the quadriceps femoris muscle-tendon unit (MTU) level. However, due to the associated decoupling between MTU and muscle fascicle length changes, it remains unclear whether a rowing cycle causes active stretch at the muscle level. Fifteen young, sub-elite, male rowers (19.5 ± 1.6 yr; 1.94 ± 0.06 m; 91.9 ± 5.4 kg; rowing experience: 7.5 ± 2.8 yr) performed randomised 60-s rowing intervals using a traditional style at a low (LiR) and high inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Rowing, which involves repetitive muscular motion, is a highly physiologically demanding competitive sport. Each rowing cycle is characterized by a stretching–shortening cycle (SSC) at the muscle–tendon unit ( Held et al, 2022 ). Muscle tone and stiffness have been shown to affect the effectiveness of SSCs ( Ishikawa et al, 2006 ; De Ste Croix et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rowing, which involves repetitive muscular motion, is a highly physiologically demanding competitive sport. Each rowing cycle is characterized by a stretching–shortening cycle (SSC) at the muscle–tendon unit ( Held et al, 2022 ). Muscle tone and stiffness have been shown to affect the effectiveness of SSCs ( Ishikawa et al, 2006 ; De Ste Croix et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the widespread applications of eccentric muscle functioning, it is perhaps unsurprising that eccentric muscle behaviour can commonly be observed in humans in a variety of muscles and during a range of spring-driven and motor-driven locomotive activities requiring force production, energy absorption and/or utilisation of the stretch–shorten cycle. This includes but is not limited to loaded exercises involving controlled lengthening contractions of the hamstrings, such as the Nordic hamstring curl [ 141 143 ], single-leg Roman chair [ 141 ], and single-leg deadlift [ 141 ], loaded exercises involving lengthening contractions of the tibialis anterior [ 138 ], gastrocnemius and soleus [ 144 147 ], and the vastus lateralis and vastus intermedius muscles [ 148 , 149 ], downhill running [ 150 ], eccentric cycling [ 151 ], rowing [ 152 ], and countermovement and drop jumps [ 153 155 ]. As already noted, small fascicle stretches have also been observed in the triceps surae during the spring-driven activities of walking [ 88 , 89 ], running [ 70 , 89 ], sprinting [ 127 ] and submaximal hopping [ 90 , 128 ].…”
Section: Models Of Locomotionmentioning
confidence: 99%
“…During certain locomotive tasks, the degree of fascicle stretching that presents also appears to share a relationship with intensity. For example, it has been demonstrated that the duration, amplitude and velocity of active fascicle stretches increase in the vastus lateralis with heightened rowing intensities [ 152 ]. Similarly, drop jumps from relatively high heights result in sudden stretches of the muscle fascicles located in the triceps surae [ 153 , 154 ].…”
Section: Models Of Locomotionmentioning
confidence: 99%
“…However, this energy efficient contraction mode is not apparent in all locomotor activities. Recent studies examining muscle behaviour during race walking and rowing, showed that fascicles followed the stretch-shortening cycle of the MTU, resulting in less efficient contractile patterns (Cronin et al, 2016; Held et al, 2022).…”
Section: Introductionmentioning
confidence: 99%